2015
DOI: 10.1039/c5ra03337c
|View full text |Cite
|
Sign up to set email alerts
|

Acceptorless dehydrogenative lactonization of diols by Pt-loaded SnO2 catalysts

Abstract: We report herein a new heterogeneous catalytic system for dehydrogenative lactonization of various diols under solvent-free and acceptor-free conditions using 1 mol% of Pt-loaded SnO 2 , providing the first successful example of acceptorless lactonization of 1,6-hexanediol to 3-caprolactone by a heterogeneous catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Interestingly, the Cu activity in the liquid-phase was much lower than that of noble metals and an early study showed that GBL was obtained in 94% yield with Ru/AlO(OH) at 110 °C in 32 h and in dilute conditions [466]. A comparative study of metal activity on SnO 2 at 180 °C highlighted that the reactivity order of was Pt > Ir > Ni > Pd > Co > Rh > Cu > Re > Ag while it was Pt > Rh > Pd when supported on rutile TiO 2 in photocatalytic conditions [467,468]. Interestingly, Pt required different supports than Cu: ZrO 2 or MgO were inactive while SnO 2 or Al 2 O 3 catalyzed the reaction.…”
Section: Liquid-phasementioning
confidence: 97%
“…Interestingly, the Cu activity in the liquid-phase was much lower than that of noble metals and an early study showed that GBL was obtained in 94% yield with Ru/AlO(OH) at 110 °C in 32 h and in dilute conditions [466]. A comparative study of metal activity on SnO 2 at 180 °C highlighted that the reactivity order of was Pt > Ir > Ni > Pd > Co > Rh > Cu > Re > Ag while it was Pt > Rh > Pd when supported on rutile TiO 2 in photocatalytic conditions [467,468]. Interestingly, Pt required different supports than Cu: ZrO 2 or MgO were inactive while SnO 2 or Al 2 O 3 catalyzed the reaction.…”
Section: Liquid-phasementioning
confidence: 97%
“…549 Silica supported copper is able to generate ε-caprolactone alongside 1-hexanol and 1,6-hexanediol, 550 and Pt-loaded SnO 2 can be used to lactonize 1,6hexanediol with an 86% yield. 551 Generally, the synthesis of ε-caprolactone is carried out by the Baeyer−Villiger oxidation of cyclohexanone, which in turn can be derived from bio-derived anisole via a hydrogenation and oxidation process (Figure 45). 552,553 However, there are still opportunities to improve this well-developed synthetic route.…”
Section: Lactonesmentioning
confidence: 99%
“…For example, Heeres et al carefully optimized a four-step route to ε-caprolactone with an overall selectivity of 95% . Silica supported copper is able to generate ε-caprolactone alongside 1-hexanol and 1,6-hexanediol, and Pt-loaded SnO 2 can be used to lactonize 1,6-hexanediol with an 86% yield …”
Section: Cyclic Monomersmentioning
confidence: 99%
“…16−20 Shimizu and co-workers reported that supported Pt catalysts were effective for the dehydrogenative synthesis of esters. 21,22 Recently, much attention has also been paid to the development of an efficient catalytic system with abundant first-row transition metals. Particularly, many examples have demonstrated that supported Cu catalysts are highly effective for the dehydrogenative transformation of alcohols to the corresponding carbonyl compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Following this breakthrough, a series of homogeneous catalysts based on transition-metal complexes, such as Ru, Rh, Ir, Re, Os, and Mn, have been developed. On the other hand, efficient organic synthesis with heterogeneous catalysts is of great significance from the perspective of green and sustainable chemistry. Shimizu and co-workers reported that supported Pt catalysts were effective for the dehydrogenative synthesis of esters. , Recently, much attention has also been paid to the development of an efficient catalytic system with abundant first-row transition metals. Particularly, many examples have demonstrated that supported Cu catalysts are highly effective for the dehydrogenative transformation of alcohols to the corresponding carbonyl compounds. Dehydrogenative synthesis of esters from alcohols has been achieved by the use of supported Cu catalysts, and the availability of ZrO 2 as a support for Cu-catalyzed dehydrogenative synthesis of esters has also been explored.…”
Section: Introductionmentioning
confidence: 99%